2001
DOI: 10.1177/0143034301221005
|View full text |Cite
|
Sign up to set email alerts
|

Children's Drawings

Abstract: Research suggests that children's drawings are reflective of their culture. In the drawings of seven and eight year old children from Japan and the United States it was found that Japanese children drew significantly fewer smiles, a higher number of details and larger figures. Findings are interpreted within cultural differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…The authors found that German children drew tadpoles about 44% taller and with more head details than the Madagascan children. These findings are in line with comprehensive cross-cultural research on conventional human figure drawings demonstrating substantial cultural differences with regard to figure size (Meili-Dworetzki, 1981; Aronsson and Andersson, 1996; Payne, 1996; Richter, 2001), as well as variety and shape of details (Wilson and Wilson, 1984; La Voy et al, 2001; Cherney et al, 2006; Yusuf, 2010). …”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The authors found that German children drew tadpoles about 44% taller and with more head details than the Madagascan children. These findings are in line with comprehensive cross-cultural research on conventional human figure drawings demonstrating substantial cultural differences with regard to figure size (Meili-Dworetzki, 1981; Aronsson and Andersson, 1996; Payne, 1996; Richter, 2001), as well as variety and shape of details (Wilson and Wilson, 1984; La Voy et al, 2001; Cherney et al, 2006; Yusuf, 2010). …”
Section: Introductionsupporting
confidence: 79%
“…Thus, in line with the cultural variability of emotional expressions and responses (Markus and Kitayama, 1991; Matsumoto, 1991; Tsai et al, 2006; Mesquita, 2007), differences have been observed in children’s depiction of the mouth in more elaborated self-drawings (La Voy et al, 2001; Gernhardt et al, 2013, 2014b). Likewise, variability in the number of depicted facial features across cultures has been explained by differences in children’s early interactional experiences.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Fordi børns tegninger kan fungere som en nonverbal traedesten til børns erfarings-og følelsesverden (Cox, 2005;Jolley, 2010;Koppitz, 1968), kan samtaler om børns familietegninger forventes at give et kendskab til børns relationelle oplevelser inden for rammerne af deres familie (Cherney, Seiwert, Dickey, & Flichtbeil, 2006;Gernhardt, Rübeling, & Keller, 2013;La Voy, 2001). I dette projekt er disse rammer bl.a.…”
Section: Tegning Som Metode Inden For Børneforskningunclassified
“…Belirtilen bu noktalar çocuk çizimlerinin duygusal uyumlarına ilişkin olarak değerlendirildiğinde de geçerlidir (Catte ve Cox, 1999;Jolley ve Vulic-Prtoric, 2001). Son zamanlardaki çalışmalarda ise çocukların çizimlerinden psikolojik açıdan durumlarını tasvir etmek, algı ve kavrayışlarını tanımlamak ön plana çıkmaktadır (Kress, 1997;Steele, 1999;Ring, 2006;Stanczak, 2007 Machover (1949) ve Koppitz (1968Koppitz ( , 1984 çocukların çizimlerini önce gelişimsel ardından duygusal açıdan ele alıp incelemişlerdir. Özellikle Koppitz (1968), çocuklarda birtakım duygusal bozuklukların teşhis edilmesinde "Bir Adam Çiz" yaklaşımından yararlanmış ve özel işaretlerin yorumlanmasında alternatif fikirler öne sürmüştür.…”
Section: Introductionunclassified